Progress in Water, Sanitation and Hygiene (WASH) coverage and potential contribution to the decline in diarrhea and stunting in Ethiopia - Girma, Meron; Hussein, Alemayehu; Norris, Tom; Genye, Tirsit; Tessema, Masresha; Bossuyt, Anne; van Zyl, Cornelia (Wiley, 2024)
Inadequate safe water supply and poor sanitation and hygiene continue to be important risk factors for diarrhoea and stunting globally. We used data from the four rounds of the Ethiopian Demographic and Health Survey and applied the new World Health Organization (WHO)/UNICEF Joint Monitoring Program (JMP) service standards to assess progress in water, sanitation and hygiene (WASH) coverage between 2000 and 2016. We also performed an age-disaggregated pooled linear probability regression analysis followed by a decomposition analysis to determine whether changes in WASH practices have contributed to the changing prevalence of diarrhoea and stunting in children under 5 years of age. We observed a significant increase in the coverage of safe drinking water and adequate sanitation facilities over the period. At the national level, the use of a basic water source increased from 18% in 2000 to 50% in 2016. Open defecation declined from 82% to 32% over the same period. However, in 2016, only 6% of households had access to a basic sanitation facility, and 40% of households had no handwashing facilities. The reduction in surface water use between 2000 and 2016 explained 6% of the decline in diarrhoea observed among children aged 0–5 months. In children aged 6–59 months, between 7% and 9% of the reduction in stunting were attributable to the reduction in open defecation over this period. Despite progress, improvements are still needed to increase basic WASH coverage in Ethiopia. Our findings showed that improvements in water and sanitation only modestly explained reductions in diarrhoea and stunting.